Identification, molecular evolution, and expression analysis of the transcription factor Smad gene family in lamprey. (August 2021) - Zhong, Zhilin; Wu, Tong; Zhu, Ting; Pang, Yue; Li, Qingwei; Su, Peng
Highlights: Smad gene family was identified from lamprey after screening of a leukocytes cDNA library for the first time. We researched the molecular evolution of the Smad gene family, and described tissue-specific expression of Lr-Smads. We found that Lr-Smad might play a key role in the immune response of lamprey. Our research provides crucial information regarding the regulatory activity of Smads during the evolution. Abstract: Transcription factor small mothers against decapentaplegic (Smad) family SMAD proteins are the essential intracellular signal mediators and transcription factors for transforming growth factor β (TGF-β) signal transduction pathway, which usually exert pleiotropic actions on cell physiology, including immune response, cell migration and differentiation. In this study, the Smad family was identified in the most primitive vertebrates through the investigation of the transcriptome data of lampreys. The topology of phylogenetic tree showed that the four Smads (Smad1, Smad3, Smad4 and Smad6) in lampreys were subdivided into four different groups. Meanwhile, homology analysis indicated that most Smads were conserved with typical Mad Homology (MH) 1 and MH2 domains. In addition, Lethenteron reissneri Smads (Lr-Smads) adopted general Smads folding structure and had high tertiary structural similarity with human Smads (H-Smads). Genomic synteny analysis revealed that the large-scale duplication blocks were not found in lamprey genome and neighbor genes of lamprey Smads presented dramatic differences compared with jawed vertebrates. Importantly, quantitative real-time PCR analysis demonstrated that Smads were widely expressed in lamprey, and the expression level of Lr-Smads mRNA was up-regulated with different pathogenic stimulations. Moreover, depending on the weighted gene co-expression network analysis (WGCNA), four Lr-Smads were identified as two meaningful modules (green and gray). The functional analysis of these two modules showed that they might have a correlation with ployI:C. And these genes presented strong positive correlation during the immune response from the results of Pearson's correlation analysis. In conclusion, our results would not only enrich the information of Smad family in jawless vertebrates, but also lay the foundation for immunity in further study.